The Influence Of Service Features, Perceived Convenience And Financial Literacy In The Decision To Use Ovo E-Wallet On Generation Z Of Bengkulu City - Heskyel Pranata Tarigan; Karona Cahya Susena; Yudi Irawan Abi (Utan Kayu Publishing, 2024)
The purpose of this study was to determine the effect of service features, perceived ease and financial literacy on the decision to use the OVO E-Wallet in Bengkulu City. This study is a type of quantitative research. The population used in this study were OVO E-Wallet users in Bengkulu City. This study used incidental sampling techniques or non-probability sampling, so that a research sample of 100 respondents was obtained from Generation Z in Bengkulu City. The collection of respondent data was distributed via Google Form.The results of the multiple linear regression analysis are the equation Y = 1.566 + 0.621 X1 + 0.253 X2 + 0.212 X3 +e, this illustrates a positive regression direction, meaning that the service feature variables (X1), perceived ease (X2) and financial literacy (X3) have a positive influence on the decision to use (Y) in Generation Z in Bengkulu City.From the results of the calculation using SPSS version 25.0, the coefficient of determination of R square can be seen as 0.842. This means that the value of service features (X1), perceived ease (X2) and financial literacy (X3) influence the decision to use (Y) by 84.2% while the remaining 15.8% is influenced by other variables not examined in this study. The results of the t-test at a significance level 0.05 explain that partially service features (X1), perceived ease (X2) and financial literacy (X3) have a significant influence on the decision to use (Y) in Generation Z of Bengkulu City. The results of the f-test are smaller than 0.000, so the variables of service features (X1), perceived ease (X2) and financial literacy (X3) have a significant influence on the decision to use (Y) in Generation Z of Bengkulu City.